Comedy’s Double Negation of Meaning in Post-war European Theater - Anna Street (Sillages Critiques)
Through selected close readings from plays by Arthur Adamov and Samuel Beckett, this article examines how language is herein used against itself to expose the impossibility of meaninglessness. By replacing significance with mere surface sounds, language emerges from these plays as a carrier of unexpected—and inescapable—meaning. Tracing a series of comic reversal techniques common to both Adamov and Beckett, famously grouped together under the moniker Theater of the Absurd, the author demonstrates how the attempt to deprive words of sense-making is repetitiously usurped by other sensory elements which doggedly invest the striving for senselessness with profound ambiguity, against all odds.